Challenges facing SDCs in the management of school development in Mt Darwin of Mashonaland Central - Mukandi, Lawrence (Midlands State University, 2020)
The objective of the study is to unearth the challenges that SDCs are facing in the management of school development. This chapter gives precedence to all the other chapters and it begins with giving an overview of how SDCs came into being. The legal framework governing the operations of SDCs and their core functions. The chapter then proceeds to research questions, significance study, limitations and delimitations then ends with assumptions of the study